The Effect of Using an Online Learning Module (Google Sites) on Student Attention in the Developmental Psychology Course - Dewi Rika Juita; Nilna Azizatus Shofiyyah; Nur Saepudin; Alif Hanafi; Imam Baehaqi (CV. Edujavare Publishing, 2026)
The purpose of this study was to examine whether the use of Google Sites as an online learning module significantly influences students' learning attention in the Developmental Psychology course. The study involved 15 second-semester students enrolled in the Islamic Education (PAI) Study Program at STAI Siliwangi Garut. A quantitative research approach was employed, with data collected through a questionnaire administered via Google Forms. Data were analyzed using Simple Linear Regression, as the study focused solely on determining the effect of Google Sites as an online learning module on students' learning attention. The findings revealed that, at a significance level of 0.05, the significance value was 0.000, indicating a statistically significant effect of Google Sites on students' learning attention. The correlation coefficient (R) was 0.880, while the coefficient of determination (R²) was 0.774. These results indicate that the use of Google Sites as an online learning module significantly affects students' learning attention in the Developmental Psychology course, accounting for 77.4% of the variance in learning attention, whereas the remaining 22.6% is attributable to other factors not examined in this study. Furthermore, the estimated regression equation was Y = 8.554 + 0.857X, indicating that each one-unit increase in the use of Google Sites as an online learning module is associated with an increase of 0.857 units in students' learning attention.